2000
DOI: 10.1007/s001060050638
|View full text |Cite
|
Sign up to set email alerts
|

Psychische Belastung, Informiertheit und Behandlungserwartung von Eltern mit einem Cochlear Implant versorgten Kind

Abstract: The psychological state of parents during the critical phase, after a diagnosis of deafness has been made for their child, has to be considered. Even after an initial phase of shock, parents seemed to be stressed to an extent that required therapeutic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 7 publications
1
6
0
3
Order By: Relevance
“…The time immediately after the diagnosis (T1 for the hearing aid parents) is perceived as the most stressful, and burdens the parents with the greatest loss of quality of life. This result corroborates both clinical observations and the retrospective evaluation on the part of the parents in previous studies (Richter et al, 2000;Spahn et al, 2002a). The data also confirm the clinical experience that marked relief is experienced by the cochlear implant parents after initial fitting: that is, when preexamination and implantation are completed.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…The time immediately after the diagnosis (T1 for the hearing aid parents) is perceived as the most stressful, and burdens the parents with the greatest loss of quality of life. This result corroborates both clinical observations and the retrospective evaluation on the part of the parents in previous studies (Richter et al, 2000;Spahn et al, 2002a). The data also confirm the clinical experience that marked relief is experienced by the cochlear implant parents after initial fitting: that is, when preexamination and implantation are completed.…”
Section: Discussionsupporting
confidence: 95%
“…Differentiating the role of possible influential variables, Hintermair (2000) singled out degree of social support as an important modifying variable in parents' subjective experience of stress. Richter, Spahn, Zschocke, Leuchter, Laszig, and Löhle (2000) reported that parents of children with cochlear implants retrospectively assess the phases of diagnosis, preexamination, and implantation as particularly laden with psychic stress. Spahn and colleagues (2001) found that, on the basis of heightened psychic stress as indicated by the SCL-90-R and parental interest in psychosocial supportive measures, a need for psychosocial counseling could be assumed in 18% of the 103 parents they studied.…”
Section: Parental Distress: the Initial Phase Of Hearing Aid And Cochmentioning
confidence: 99%
“…This information is important for cochlear implant teams to be used in family counseling, in helping parents to set realistic expectations. Although reports have been rather consistent that parents' preoperative expectations have been realistic [7,11,16,33], parental expectations are known to change as a function of their child's progress [33,38,39]. Parents who perceive the implant as a beneficial device will probably take more care of its maintenance and support its use better than parents that do not think so.…”
Section: Discussionmentioning
confidence: 95%
“…They provide information on real-life situations and help to draw a broad picture of a person's level of activities and ability to participate in different social environments. Indeed, interviews and parental questionnaires have been used in those still relatively few studies conducted to explore the parental expectations [6][7][8][9][10][11][12], satisfaction with implant habilitation [6,7,[13][14][15][16], parental stress [11,17,18], and the quality of life of implanted children and their families [6,11,13,[17][18][19]. Because of cultural variation and differences between health care systems, change in quality of life after implantation needs to be studied in countries representing different kinds of cultures and views on preferred communication modes.…”
mentioning
confidence: 99%
“…Thus, numerous studies have shown that the parents of children with cochlear implants even have higher stress level than do parents of children who use hearing aids (1517). Some studies have shown that parental stress increases with increasing duration of rehabilitation (16, 1820). Several reasons have been suggested to be associated with this increase, including encounters with specific requirements for children’s education, school, increased social interactions, and high level of expectations, although study results are controversial (8).…”
Section: Discussionmentioning
confidence: 99%